Bacteroides fragilis Enterotoxin Upregulates Matrix Metalloproteinase-7 Expression through MAPK and AP-1 Activation in Intestinal Epithelial Cells, Leading to Syndecan-2 Release - Jong Ik Jeon (MDPI AG, 2021)
Bacteroides fragilis enterotoxin (BFT) produced by enterotoxigenic B. fragilis (ETBF) causes colonic inflammation. BFT initially contacts intestinal epithelial cells (IECs) and affects the intestinal barrier. Although molecular components of the gut epithelial barrier such as metalloproteinase-7 (MMP-7) and syndecan-2 are known to be associated with inflammation, little has been reported about MMP-7 expression and syndecan-2 shedding in response to ETBF infection. This study explores the role of BFT in MMP-7 induction and syndecan-2 release in IECs. Stimulating IECs with BFT led to the induction of MMP-7 and the activation of transcription factors such as NF-κB and AP-1. MMP-7 upregulation was not affected by NF-κB, but it was related to AP-1 activation. In BFT-exposed IECs, syndecan-2 release was observed in a time- and concentration-dependent manner. MMP-7 suppression was associated with a reduction in syndecan-2 release. In addition, suppression of ERK, one of the mitogen-activated protein kinases (MAPKs), inhibited AP-1 activity and MMP-7 expression. Furthermore, the suppression of AP-1 and ERK activity was related to the attenuation of syndecan-2 release. These results suggest that a signaling cascade comprising ERK and AP-1 activation in IECs is involved in MMP-7 upregulation and syndecan-2 release during exposure to BFT.